2010
DOI: 10.1186/1758-2652-13-s4-p181
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic and pharmacogenetic analysis of nevirapine in hypersensitive and tolerant HIV‐infected patients from Malawi

Abstract: 7‐11 November 2010, Tenth International Congress on Drug Therapy in HIV Infection, Glasgow, UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
6
2
Order By: Relevance
“…Two single nucleotide polymorphisms (SNPs) in the CYP2B6 gene, c.516G>T (rs3745274) and c.983T>C (rs28399499), have been shown to affect CYP2B6 enzyme activity and NVP plasma concentration (Dickinson et al, 2014;Hoffman et al, 2001). However, this has yet to be demonstrated for the Zimbabwean population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two single nucleotide polymorphisms (SNPs) in the CYP2B6 gene, c.516G>T (rs3745274) and c.983T>C (rs28399499), have been shown to affect CYP2B6 enzyme activity and NVP plasma concentration (Dickinson et al, 2014;Hoffman et al, 2001). However, this has yet to be demonstrated for the Zimbabwean population.…”
mentioning
confidence: 99%
“…However, this has yet to be demonstrated for the Zimbabwean population. Both variants, one in exon 4, CYP2B6 c.516T (p. 172H), and the second in exon 7, CYP2B6 c.983C (p. 328Thr), have been associated with a significant loss of function of the resultant protein, and therefore higher levels of NVP compared to the alternative alleles (Code et al, 1997;Dickinson et al, 2014;Gounden et al, 2010;Haas et al, 2009;Hofmann et al, 2008;Rotger et al, 2007).…”
mentioning
confidence: 99%
“…82 These findings add to a growing number of observations showing that multiple processes including pharmacological and immunological mechanisms contribute to ADRs that may be mediated by the parent drug, and that dose dependency is likely a key feature of both on-target and off-target ADRs ( Figure 1). [85][86][87][88][89] Drug-specific models: allopurinol Allopurinol is a xanthine oxidase inhibitor that is used to treat hyperuricemia and is associated with an IM-ADR of variable, but primarily cutaneous, phenotype in approximately 2% of patients who initiate therapy. In 2005, it was demonstrated that the HLA-B*58:01 genotype is associated with allopurinol-induced SJS/TEN and DRESS in persons of Han Chinese ancestry (100% negative predictive value, 3% positive predictive value).…”
Section: Drug-specific Models: Abacavirmentioning
confidence: 99%
“…These correlations have led to recommendations to reduce the EFV dosage in order to prevent occurrence of the adverse drug effects [18,24]. Individuals with the CYP2B6*6 allele have also been shown to have a significant increase in nevirapine plasma concentrations, which has been associated with immunologic response [19]. The use of singledose NVP to prevent perinatal vertical transmission has been reported to have pro¬longed exposures in women with the CYP2B6*6 allele, which greatly increases the risk of developing resistance mutations to NVP [25].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, studies have also been done in African populations to evaluate the clinical implications of the CYP2B6*6 allele in the use of efavirenz [15][16][17][18], and nevirapine [19][20][21]. CYP2B6*6 has been associated with higher efavirenz plasma concentrations due to lower clearance rates, which may lead to CNS side effects [22,23].…”
Section: Introductionmentioning
confidence: 99%